Respuesta :

cy+3=6d-2y
cy + 2y = 6d - 3
(c + 2)y = 6d - 3
y = (6d - 3)/(c + 2)
I will do my best to explain what is done, but feel free to ask if you have questions on what I did:
[tex]cy+3=6d-2y[/tex]
bring all the "y"s to one side
[tex]cy+3-3=6d-2y-3[/tex]
[tex]cy+2y=6d-3-2y+2y[/tex]
this should be your result...
[tex]cy+2y=6d-3[/tex]
now divide y out to isolate it:
[tex]y(c+2)=6d-3[/tex]
then divide our c+2 so your y is alone
[tex] \frac{y(c+2)}{c+2}= \frac{6d-3}{c+2} [/tex]
you should get this as your answer:
[tex]y= \frac{6d-3}{c+2} [/tex]